Students’ Experiences of Enhancing Language Skills through Self-Initiated English Exposure - Al Jabbar, Bagoes Sanyoto; Asmiyah, Siti; Nafidah, Hikmah (ICONELT, 2024)
The objective of this descriptive quantitative study is to explore students' experience in self-initiated English exposure and how they reflect on the effects of such exposure to their English language skills. This approach was chosen because of its features that allow for the systematic collection and analysis of numerical data on students’ experiences of accessing and using various media for their English learning. This method provides a powerful framework for examining how students reflect on how self-initiated English exposure affects students’ language skills. A close-ended questionnaire was distributed to a class grade 11 at a state senior high school in Sidoarjo and 32 students responded to the questionnaire. The key finding shows that for self-initiated English exposure beyond the classroom, students mainly use digital media such as music and movies. The students also agree that such exposure to the media has a discernible impact on their English language skills. Students confirm that their language skills are being more developed with content or exposure that matches the language skills they want to develop, which each student has a different interest. In summary, students’ responses highlight that self-initiated English exposure gives a positive impact in enhancing students' language skills by matching appropriate content with the skills that are needed to develop. The findings imply that in ELT, teachers need to encourage more self-initiated activities by giving them prompts for independent learning adhering to the learning objective but still with a certain degree of flexibility on the types of media or mode students can expose themselves to.